Etnoekonomi Ubi Kayu (Manihot utilissima) Sebagai Bahan Pangan Berbasis Kearifan Lokal Pada Masyarakat Buton - Syamsuri, Syamsuri (Universitas Batanghari Jambi, 2024)
Ethnoeconomics is a branch of ethnobotany that examines the economic value or use of a plant in everyday life by an ethnic group based on local wisdom, one of which is food. Local wisdom is a tradition in an area that is passed down from generation to generation and can improve the economy if managed properly. The aim of the research is that Ethnoeconomics is a branch of ethnobotany that examines the economic value or use of a plant in everyday life by an ethnic group based on local wisdom. The research method uses observation and interviews. The data obtained are in the form of qualitative data and quantitative data. Data analysis was carried out in the form of descriptions of cassava based on local wisdom carried out descriptively, while quantitative analysis was carried out to calculate the economic potential of cassava cultivation using the acceptance and income formula. The results of the study showed that cassava cultivation based on local wisdom has economic potential because it can generate profits of Rp. 2,450,000.00. The ethnoeconomics of cassava food is processing it into traditional food including kasoami, kabuto, doko-doko and vegetables.